E. Alexander Powell papers - Powell, E. Alexander (Edward Alexander), 1879-
Correspondence, diaries, speech, writings, biographical material, Northrup and Powell family papers, photographs, drawings, and other papers relating to Powell's writings, travel, and personal life. Family papers include correspondence and diaries of Powell's wife, Jessie Northrup Powell, and correspondence of his parents, Edward A. and Lucy Powell. Correspondents include Poultney Bigelow, William Jennings Bryan, Warren G. Harding, J. J. Jusserand, John J. Pershing, Ralph Pulitzer, Theodore Roosevelt, Ellery Sedgwick, and Leonard Wood.
Library of Congress Prints and Photographs Division.
Author. Died 1957.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bigelow, Poultney, -- 1855- -- Correspondence; Bryan, William Jennings, -- 1860-1925 -- Correspondence; Harding, Warren G. -- 1865-1923 -- Correspondence; Jusserand, J. J. -- 1855-1932 -- Correspondence; Pershing, John J. -- 1860-1948 -- Correspondence; Powell, Edward A. -- Correspondence; Powell, Jessie Northrup -- Correspondence; Powell, Jessie Northrup -- Diaries; Powell, Lucy -- Correspondence; Pulitzer, Ralph, -- 1879-1939 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Sedgwick, Ellery, -- 1872-1960 -- Correspondence; Wood, Leonard, -- 1860-1927 -- Correspondence; Northrup family; Powell family; Travel writing; Voyages and travels; Authors